2019
DOI: 10.1002/adma.201902118
|View full text |Cite
|
Sign up to set email alerts
|

Linear Dichroism Conversion in Quasi‐1D Perovskite Chalcogenide

Abstract: Anisotropic photonic materials with linear dichroism property are crucial components in many sensing, imaging and emerging light based quantum communication applications. Such materials play an important role as polarizers, filters, wave-plates, phase-matching elements in photonic devices and circuits. Conventional crystalline materials with optical anisotropy typically show strong unidirectional linear dichroism over a broad wavelength range and even bandgap variations along different crystal directions. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…Remarkably, the linear dichroism of PL peak P6 can reach more than 90%, being comparable to the highest values obtained among the well-known quasi-1D van der Waals materials (Fig. 3i ) 3 , 6 , 50 55 . The linear dichroism of other PL peaks can be found in Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Remarkably, the linear dichroism of PL peak P6 can reach more than 90%, being comparable to the highest values obtained among the well-known quasi-1D van der Waals materials (Fig. 3i ) 3 , 6 , 50 55 . The linear dichroism of other PL peaks can be found in Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%
“…The results further confirm the highly anisotropic PL emission. To quantify the magnitude of PL anisotropy, we define the degree of linear dichroism as , where I c o ( I cross ) denotes the PL intensity detected copolarized (cross-polarized) to the laser polarization 8 , 49 , 50 . The inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The anisotropic absorption edges were also certified through density-functional calculations of absorption coefficients for polarized light along the intrachain and interchain directions. More detailed study from Wu et al revealed a unique linear dichroism conversion behavior in the quasi-1D BaTiS3 at an optical wavelength of 0.7 μm, corresponding to the excitation photon energy of 1.78 eV [48], which is due to polarization-resolved localized joint density of states of the crystal resulting from the parallel energy bands in this optical transition energy range. Moreover, an unprecedentedly giant and broadband birefringence of up to 0.76 was confirmed in the mid-to long-wave infrared ranging from 8 to 16.7 μm.…”
Section: Batis3mentioning
confidence: 99%
“…6(a) [16]. Ideally, the polarization dependent absorption can be described as, η(θ) = ηmaxcos 2 (θ) + ηminsin 2 (θ), where θ is the angle with the main axis, which has the strongest absorption (ηmax), ηmax is the absorption along the second axis that is orthogonal to the main axis for all the materials discussed here [18,37,40,46,48,183]. For the other materials with lower symmetry, such as ReS2 [184] and ReSe2 [185], the main axis and second axis are no longer orthogonal, thus, it needs new equation to describe the angle-dependent absorption.…”
Section: Polarization Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation